2020
DOI: 10.1109/jstars.2020.3019696
|View full text |Cite
|
Sign up to set email alerts
|

Summer Nights in Berlin, Germany: Modeling Air Temperature Spatially With Remote Sensing, Crowdsourced Weather Data, and Machine Learning

Abstract: Urban areas tend to be warmer than their rural surroundings, well-known as the "urban heat island" effect. Higher nocturnal air temperature (T air ) is associated with adverse effects on human health, higher mortality rates, and higher energy consumption. Prediction of the spatial distribution of T air is a step toward the "Smart City" concept, providing an early warning system for vulnerable populations. The study of the spatial distribution of urban T air was thus far limited by the low spatial resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Differences in the setup of the stations likely affect results regarding the contribution of scales; yet to what extent is not understood. • Follow-up studies could explore the use of machine learning (ML) techniques that are already used to study and predict UHI spatial patterns (Straub et al, 2019;Gardes et al, 2020;Vulova et al, 2020). Simultaneously, existing ML-based techniques could be improved by considering the mesoscale heterogeneity of the urban environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the setup of the stations likely affect results regarding the contribution of scales; yet to what extent is not understood. • Follow-up studies could explore the use of machine learning (ML) techniques that are already used to study and predict UHI spatial patterns (Straub et al, 2019;Gardes et al, 2020;Vulova et al, 2020). Simultaneously, existing ML-based techniques could be improved by considering the mesoscale heterogeneity of the urban environment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of nontraditional and opportunisticsensing technologies in meteorological and climatological research, such as smartphones (Overeem et al, 2013b;Mass and Madaus, 2014;Droste et al, 2017), cars (Haberlandt and Sester, 2010;Mahoney and O'Sullivan, 2013;Bartos et al, 2019), commercial microwave links (Messer et al, 2006;Zinevich et al, 2009;Overeem et al, 2013a;Chwala and Kunstmann, 2019), wrist-mounted wearables (Nazarian et al, 2020), and privately owned citizen weather stations (CWSs), e.g., Wolters and Brandsma (2012), Bell et al (2015), de Vos et al (2017, Meier et al (2017), Fenner et al (2019, Droste et al (2020), and Mandement and Caumont (2020), have shown to provide additional and reliable information, thus, highlighting a multitude of possible applications in research and beyond (de Vos et al, 2019;Nipen et al, 2020). To study urban air temperatures and the UHI effect, data from CWSs have been used in a variety of studies (Steeneveld et al, 2011;Chapman et al, 2017;Fenner et al, 2017;de Vos et al, 2020;Feichtinger et al, 2020;Venter et al, 2020;Vulova et al, 2020), focusing on different cities. One major advantage of CWSs over traditional meteorological stations is their large number within a single city (Meier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such non-traditional, opportunistic sources of data are, e.g., smartphones (e.g., Overeem et al, 2013b;Mass and Madaus 2014;Droste et al, 2017), smart wearable devices (Nazarian et al, 2021), cars (e.g., Haberlandt and Sester 2010;Bartos et al, 2019), commercial microwave links (e.g., Messer et al, 2006;Overeem et al, 2013a;Chwala and Kunstmann 2019), and privately-owned weather stations, called citizen weather stations (CWS) in the following (e.g., Steeneveld et al, 2011;Wolters and Brandsma 2012;Bell et al, 2013;Madaus et al, 2014;Chapman et al, 2017;de Vos et al, 2017;Venter et al, 2021). Each type of these data sources alone or multiple combined can be used in different meteorological and climatological applications, such as weather forecast (e.g., Mass and Madaus, 2014;Nipen et al, 2020), operational weather monitoring (e.g., de Vos et al, 2019), mesoscale model evaluation (e.g., Hammerberg et al, 2018), hydrometeorological analyses and modelling (e.g., Smiatek et al, 2017;de Vos et al, 2020), high-resolution mapping of air temperature (e.g., Venter et al, 2020;Vulova et al, 2020;Zumwald et al, 2021), thermal-comfort assessment (Nazarian et al, 2021), and urban climate investigations (e.g., Fenner et al, 2017Fenner et al, , 2019Droste et al, 2020;Feichtinger et al, 2020). The potential of CWS data is especially large for cities, where population density and thus also CWS network density is high and where traditional meteorological observations are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…CrowdQC is a statistically-based QC with four main and three optional QC levels that are applied sequentially, removing erroneous data based on the assumption that the whole crowd of CWS knows more than each individual station ("wisdom of the crowd"). Since its release, CrowdQC has successfully been applied in a number of studies to qualitycontrol CWS ta data for further analyses (e.g., Fenner et al, 2019;Feichtinger et al, 2020;Venter et al, 2020Venter et al, , 2021Vulova et al, 2020;Benjamin et al, 2021;Potgieter et al, 2021;Zumwald et al, 2021). Its large-scale applicability was only recently demonstrated by the study of Venter et al (2021), using CrowdQC to quality-control data from >50,000 CWS in 342 urban regions in Europe for a summer month.…”
Section: Introductionmentioning
confidence: 99%
“…In urban environments, ET is inversely proportional to the intensity of the urban heat island (UHI) effect (Wang et al, 2020). The UHI effect adversely affects the health and quality of life of urban residents (Kovats and Hajat, 2008;Scherer et al, 2013;Vulova et al, 2020). As most of the world population https://doi.org/10.5194/hess-2021-283 Preprint.…”
Section: Introductionmentioning
confidence: 99%